Faktor Penghambat Pelaksanan Layanan Bimbingan dan Konseling di SMK Se Kabupaten Tegal Pada Masa Covid-19 - Eka Yanuar Putri (Dharmas Education Journal (DE_Journal), 2021)
Guidance and counseling services need to be organized as a concrete manifestation of the implementation of guidance and counseling services. The phenomenon that occurs in the field is that the implementation of guidance and counseling services has not been implemented optimally due to obstacles, both internal and external. The purpose of this study is to determine the inhibiting factors in the implementation of guidance and counseling services in Vocational High Schools in Tegal Regency. The results of the study of the inhibiting factors for the implementation of guidance and counseling services in Vocational High Schools in Tegal Regency, namely the inhibiting factors for the implementation of BK services, seen from the competence of the counselor included in the high criteria (20%). The inhibiting factor for the implementation of BK services is seen from the factor of the workload of the counselor, which is included in the low criteria (13%). The factor inhibiting the implementation of BK services is seen from the factor of the principal, which is included in the moderate criteria (18%). The inhibiting factor for the implementation of BK services is seen from the teacher factor in the medium category (19%). The factor inhibiting the implementation of BK services is seen from the student factor included in the moderate criteria (19%). And the last is the inhibiting factor for the implementation of BK services seen from the facilities and infrastructure factors that are included in the low criteria (11%).